Strategi Pemasaran Sekolah Pasca Pandemi Covid-19 - Ase Kurniawan (Jambura Journal of Educational Management, 2023)
The change in the status of the pandemic to endemic provides new enthusiasm for education managers to continue the struggle to educate the nation's life. Education managers are competing to promote their institutions so that consumers can use their services again, including Serba Bakti High School. Various strategies are implemented from very simple to quite complex strategies. The goal is to promote schools as institutions engaged in services and by using the services of these schools can facilitate customers in achieving their goals. From this, the researchers focused on the marketing strategy of the Serba Bakti High School with the aim of seeing and photographing the strategies carried out by the Serba Bakti High School after the covid-19 pandemic. The method used is descriptive qualitative with data collection techniques through interviews, observations and documentation studies. Data analysis techniques used include data reduction, data exposure and verification and triangulation. The results of the study show that SMA Serba Bakti uses a strategy that includes product, price, promotion, place, process, people, physical evidence. oriented towards religion and entrepreneurship, price includes discounts and scholarships for students in the surrounding environment and outstanding students, the promotion is divided into two parts, namely short-term promotions such as distributing pamphlets on social media, presentations at school and long-term promotions such as establishing cooperation with potential schools and surrounding villages. Place, a green school environment and complete facilities for the learning process of students as well as trading facilities for students who are members of entrepreneurial organizations. The student registration process can be done online and offline. There is counseling guidance to facilitate outstanding students and students who have learning disabilities. People, educators are strata II and undergraduate graduates and education staff are strata one and high school graduates. Physical evidence, the Serba Bakti High School environment is a formal educational environment from Kindergarten to college and non-formal education such as Islamic boarding schools, ta'lim assemblies and others